STRATEGI GURU PENDIDIKAN AGAMA KATOLIK DALAM MENANGGULANGI SADNESS PADA SISWA KELAS XI DI SMA - Mimpin Sembiring; Enjelita Depari (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The strategies of Catholic Religious Education (CRE) teachers are highly important in accompanying students’ emotional and spiritual development, particularly in dealing with sadness that may influence the learning process at school. Sadness does not only affect psychological aspects, but also influences students’ physiological, cognitive, and affective dimensions in learning activities. This study focuses on describing the sadness experienced by Grade XI students and examining the strategies of Catholic Religious Education teachers in addressing sadness at SMA Swasta RK Serdang Murni Lubuk Pakam. A qualitative approach with a descriptive research design was employed. Data were collected through observation, interviews, and documentation involving Catholic Religious Education teachers, Guidance and Counseling teachers, the principal, and Grade XI students. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that students’ sadness is reflected in physiological aspects such as sad facial expressions and bodily responses, cognitive aspects such as decreased concentration, changes in thinking patterns, and reduced memory ability, as well as affective aspects such as social withdrawal, low empathy, and decreased learning motivation. The strategies of CRE teachers are implemented through their roles as faith and moral educators, spiritual mentors, role models of Christian living, facilitators of religious activities, builders of faith communities, and developers of emotionally responsive learning. These strategies play an important role in helping students manage sadness, although their impact is not yet evenly experienced; therefore, a more personal and sustainable approach is still needed. ABSTRAK Strategi Guru Pendidikan Agama Katolik (PAK) penting dalam mendampingi perkembangan emosional siswa, khususnya dalam menghadapi sadness yang dapat memengaruhi proses pembelajaran di sekolah. Sadness tidak hanya berdampak pada aspek psikologis, tetapi juga memengaruhi aspek fisiologis, kognitif, dan afektif siswa dalam aktivitas belajar. Fokus kajian ini adalah mendeskripsikan sadness yang dialami siswa kelas XI serta mengkaji strategi guru Pendidikan Agama Katolik dalam menanggulangi sadness di SMA Swasta RK Serdang Murni Lubuk Pakam. Pendekatan yang digunakan adalah kualitatif dengan jenis penelitian deskriptif. Data diperoleh melalui observasi, wawancara, dan dokumentasi dengan subjek penelitian guru Pendidikan Agama Katolik, guru Bimbingan Konseling, Kepala Sekolah, dan siswa kelas XI. Analisis data dilakukan menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan, serta diuji keabsahannya melalui triangulasi sumber dan teknik. Hasil kajian menunjukkan bahwa sadness siswa tampak pada aspek fisiologis seperti wajah murung dan respons tubuh, aspek kognitif berupa penurunan konsentrasi, perubahan cara berpikir, serta kemampuan menghafal, dan aspek afektif berupa menarik diri, rendahnya empati, serta penurunan motivasi belajar. Strategi guru PAK dilakukan melalui strategi sebagai pendidik iman dan moral, pembimbing spiritual, teladan hidup Kristiani, fasilitator kegiatan keagamaan, pembangun komunitas beriman, serta pengembang pembelajaran yang responsif terhadap kebutuhan emosional siswa. Strategi guru PAK berperan penting dalam membantu siswa mengelola sadness, meskipun dampaknya belum merata sehingga diperlukan pendekatan yang lebih personal dan berkelanjutan.